The fall armyworm (Faw) spodoptera frugiperda: a review on biology, life history, invasion, dispersion and control - Sarkowi, Fateen Noorasyiqin; Mokhtar, Anis Syahirah (Research Information, 2021)
The fall armyworm (FAW) is a most devastating pest that has great threats to the food security of the world. There are various reasons that make this pest one of the world’s most invasive species including; they are polyphagous, have a high reproduc-tive rate and they can migrate long distance. We review FAW global life history, invasions and their management.